Chinese & Japanese Infrastructure Diplomacy in Africa: A Comparative Study and Two-Sided Analysis - Yeremia Nicolaus Widjanarko; Miguel Angel Esquivias (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2026)
Objective: This research investigates the infrastructure diplomacy strategies of China and Japan in Africa, addressing a critical gap in understanding how these different approaches influence regional stability and economic development. The study contextualizes the pressing infrastructure deficits in Africa, which significantly hinder its economic growth and social progress. Design/Methods/Approach: The primary objective of this qualitative research is to explore the strategic objectives that lie behind Chinese and Japanese infrastructure investments in Africa, examining their implications for both regional and African economies along with their geopolitical dynamics. Employing a qualitative case study approach, this research utilizes document analysis, including project reports and secondary sources, to gather nuanced contextual information. Comparative analysis is conducted to identify common themes and divergent patterns in the infrastructure strategies of both economic giants, with triangulation enhancing the validity of the findings. Findings: This research reveals that China's infrastructure investments, characterized by significant loans tied to resource extraction, often lead to dependency and potential instability in recipient economies. In contrast, Japan's approach emphasizes quality infrastructure and local capacity building, fostering sustainable development and long-term partnerships. These two differing strategies reflect the evolving power dynamics within the region, highlighting implications for both international and regional relations. Originality/Value: This research contributes to the broader discourse on international relations and development studies, offering insights into how infrastructure diplomacy shapes the geopolitical landscape in Africa. Future research directions are suggested to further explore the long-term impacts of these strategies on local communities and regional cooperation. Practical/Policy implication: The findings underscore the importance of a balanced, multipolar international system in which infrastructure options contribute to regional stability and economic resilience.